Pollutant Removal Performances Of Tropical Wetland Plants In Treating Domestic Wastewater Using Mesocosm Studies - Saad, Nur Afiqah Ahmad (Universiti Sains Malaysia, 2021)
Domestic wastewater, also known as sewage, is the waste produced from residential, institutional, commercial and establishments due to human activities. Constructed wetlands have been recommended as an alternative solution to other conventional sewage treatment systems to treat wastewater with high nutrients content due to its cost-effective, environmentally friendly and sustainable characteristics. The performances of constructed wetlands depend on its flow design, vegetation, and filter media used. In this study, mesocosm studies of surface and subsurface flow constructed wetland have been tested on its removal efficiency of total suspended solids (TSS), total nitrogen (TN) and total phosphorus (TP). A total of 12 mesocosms were planted with replicates of bacopa (Bacopa Caroliniana), water hyacinth (Eichhornia crassipes), watermoss fern (Salvinia auriculata) and a control column without vegetation were used in this study. The plants were chosen as they have a fast growth characteristic, adaptability to a wide range of environmental conditions and high nutrient uptake capacity. It was observed that watermoss fern was more effective in removing TSS and TN, while water hyacinth has significant potential in removing TP. As for system comparison, subsurface flow constructed wetlands were better compared to surface flow constructed wetlands. In conclusion, subsurface flow constructed wetlands planted with watermoss fern and water hyacinth is a good combination in treating domestic wastewater.